Highly oriented platinum/iridium thin films for high-temperature thermocouples with superior precision. Issue 10 (28th February 2022) - Ma, Kexin; Cao, Lili; Luo, Fei; Zhou, Haitao; Liu, Dabo; Luo, Bingwei; Xu, Yi; Cui, Jinting; Zhao, Xiaohui
Abstract : A Pt/Ir thin-film thermocouple with well-matched interface and highly oriented thin films has superior precision owing to the fewer resulting defects in the Pt and Ir thin films with highly preferential orientation along the (111) plane. Abstract : The long-term precise high-temperature measurement of thin-film thermocouples (TFTCs) has attracted attention due to the capability of instantaneous temperature detection. However, related technologies have seen slow development, and there is no one standard TFTC yet. Here, we focus on a new strategy of reducing alloys for the easy preparation and performance enhancement of TFTCs via nanostructure and interface design. To this end, we fabricated a platinum/iridium (Pt/Ir) pure-element TFTC with a well matched interface and few defects, which demonstrated excellent long-term service stability over a high-temperature range. The corresponding polynomial fitting coefficients were ≥0.99999, indicating the accurate acquisition of temperature data. A reduced deviation (<0.21%) between three calibration cycles was obtained over a wide temperature range of 300 °C to 1000 °C, which is better than the maximum precision of a standard wire thermocouple. Superior properties are achieved because of the resulting fewer defects in the Pt and Ir thin films with highly preferential orientation along the (111) plane. The results indicate that our Pt/Ir TFTCs have significant potential for application in many domains such as thermal detection, microelectronics and aero-engines.